Near-free-standing epitaxial graphene on rough SiC substrate by flash annealing at high temperature. (August 2017) - Hu, Tingwei; Bao, Hongwei; Liu, Shuai; Liu, Xiangtai; Ma, Dayan; Ma, Fei; Xu, Kewei
Abstract: In this paper, flash annealing at high temperature (HT) is adopted to fabricate graphene through thermal decomposition of SiC. Interestingly, surface roughening will lead to near-free-standing epitaxial graphene (EG) decouple from SiC substrate. The process dependent morphology and properties of EG are studied. As compared to flat EG on SiC prepared by conventional thermal decomposition, the decoupled EG exhibits a near-free-standing feature as confirmed by scanning tunneling spectroscopy (STS). As a result, it shows dramatically increased I2D /IG ratio and red shift of 2D-band in Raman spectrum, moreover, the compressive stress in EG layer is released by 63%. The results illustrated the possibility, and the mechanism is discussed in detail. This decoupling scheme is suitable for various SiC, regardless of the stacking configuration, polar faces and surface reconstruction. It provides us a reproducible approach to fabricate near-free-standing EG, and highlight its application in high-performance electronics. Graphical abstract: